CWLFM high range resolution radar for ISAR imaging without motion compensation (2008)
This article explains how to obtain ISAR images with a continuous wave frequency linear modulation radar, not only at the theoretical level but also showing the results obtained in numerous experiments during the four-year duration of a research project funded by the Ministry of Science and Technology Spanish. Highlighting their quality and that, over the targets, there was no control or collaboration, which makes the results much more important from a practical point of view.